Peran Manajemen Laba, Kompensasi Direksi, dan Kepemilikan Saham Direksi Terhadap Agresivitas Pajak pada Industri Manufaktur di Indonesia - Ng Husin; Rosna Agustina; Anna Sofia Atichasari; Chintya Mega Pratiwi (Universitas Matana, 2020)
This study aims to examine the effect of profit management, directors 'compensation, and directors' share ownership on the tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange during the 2014-2018 period. The sample technique used in this study is using purposive sampling method. In addition, the regression analysis model used in this study is the multiple regression analysis method using IBM SPSS V.23 software. The results of this study prove that profit management variables measured by discretionary accruals (DA) and directors' share ownership variables (KSD) as measured by the percentage of share ownership owned by directors have no effect on tax aggressiveness as measured by Effective Tax Rates (ETR). However, different from the directors 'compensation variable (KD) measured by the natural logarithm of the amount of directors' compensation given during one period has a negative effect on tax aggressiveness as measured by Effective Tax Rates (ETR).